Constructing national identity: media narratives on the naturalization of football players in Indonesia - Ismail, Ahmad; Munsi, Hardiyanti; Purwanto, Semiarto Aji (Frontiers in Sports and Active Living, 2025)
This study explores how Indonesian media construct narratives surrounding the naturalization of foreign-born football players and their implications for national identity. Drawing on 52 media articles from major national outlets published between January 2022 and April 2025, the research employs a qualitative content analysis grounded in a multi-theoretical framework that includes imagined communities (Anderson), identity representation (Hall), and thick vs. thin citizenship (Oonk). The findings reveal three dominant media frames: (1) naturalized players as national assets who elevate performance and international competitiveness; (2) skepticism over their authenticity and emotional ties to Indonesia; and (3) contested implications for local talent development. While naturalization is often portrayed as a pragmatic strategy, the media also frame it as a site of negotiation between globalization and local values. By mediating public perception, the media significantly influence how naturalized players are integrated into the symbolic boundaries of national identity. This study contributes to scholarship on media, sports, and nationalism in the Global South by showing how national identity is constructed through media discourses in the era of sports globalization.